Generative AI Literacy and Students’ Academic Performance: The Mediating Role of Student Engagement in Higher Education (Patan Pragya, 2025)
Purpose: The study investigates the effectiveness of Generative AI Literacy, which includes Technical Proficiency, Critical Evaluation, Ethical Awareness, and Creative Application in influencing the academic performance of postgraduate management and education students. It also addresses the mediating role of the student engagement in the learning outcomes in the higher education.Methods: The sample was 197 postgraduate students of different stream in Kapilvastu District. Descriptive and Explanatory research design has been used to conduct the study. The questionnaire was a structured questionnaire with 7 points Likert scale used to collect data. PLS-SEM was used to evaluate the relationship between variables.Results: The findings indicate that Generative AI Literacy is an important indicator of academic performance (0.486). Embracing technical excellence and creative application not to mention other factors have the largest factor loadings but other factors including critical evaluation and ethical awareness have also made a substantial contribution. AI literacy (0.516) had a positive influence on the student engagement (0.266) and, therefore, student academic performance (0.209). The mediation analysis has established that there is indeed such a thing as student engagement being a mediator of relationship between AI literacy and academic success and that student endowed with high AI competencies are most likely to be active hence more successful in their performance. Implications: Higher education institutions need to implement structured AI literacy programs, ethical/critical use of AI tools and models of teaching that are engagement-based in order to foster academic excellence in an AI-infused learning environment.Originality: The present study is among the pioneer studies involving the application of PLS-SEM to test the multidimensional nature of Generative AI Literacy and its mediated effect on student engagement in academic performance in the environment of higher education within Nepal.